Analytical predictions of steady state tyre characteristics. (24th February 2004) - Goel, V.K.; Ramji, K.
The primary forces and moments that affect the directional control properties of wheeled vehicles are those between the road and the rolling tyre. These force and moment characteristics are non-linear functions of a large number of parameters. In this paper, an analytical approach for determining tyre tractive force, lateral force, aligning torque and overturning moment characteristics due to combined slips has been presented. The analytical model predicts these forces and moments in terms of easily measurable parameters such as contact patch area and longitudinal, lateral and vertical stiffness of the tyre.